2011
DOI: 10.1159/000324109
|View full text |Cite
|
Sign up to set email alerts
|

Erosive Tooth Wear and Consumption of Beverages among Children in the United States

Abstract: Background/Aim: Experimental studies have identified differences in the effect of physicochemical properties of beverages on the etiology of erosive tooth wear (ETW). Little is known from epidemiological studies about the relationship between ETW and consumption of juices, drinks and milk. This study examined the relationship between the consumption of juices, drinks, milk and ETW in children in the United States. Methods: The National Health and Nutrition Examinations Survey data for 2003–2004 was analyzed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
43
1
11

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 58 publications
6
43
1
11
Order By: Relevance
“…20 Considering the increasing prevalence of dental erosion in the USA, 2122 with the consumption of acidic soft drinks being the major contributing etiological factor, 22 more emphasis should be paid on nutrition education to not only limit the irreversible loss of tooth structure but also -as the present study has shown -to optimize the benefit/risk ratio of a topical fluoride treatment (e.g. varnish, gel, foam, rinse).…”
Section: Discussionmentioning
confidence: 89%
“…20 Considering the increasing prevalence of dental erosion in the USA, 2122 with the consumption of acidic soft drinks being the major contributing etiological factor, 22 more emphasis should be paid on nutrition education to not only limit the irreversible loss of tooth structure but also -as the present study has shown -to optimize the benefit/risk ratio of a topical fluoride treatment (e.g. varnish, gel, foam, rinse).…”
Section: Discussionmentioning
confidence: 89%
“…The majority have associated this problem with beverages present in the modern diet, for example wine [10][11] , sport beverages [12][13] , soft drinks [14][15][16] and juices [13][14]17 .…”
Section: Introductionmentioning
confidence: 99%
“…It ranges from 5.5 to 65.34%; at the age of 12 years from 13 to 56.1%, at the age of 15 years from 24 to 44.2%, and at the age of 18 years from 22.2 to 55.5%. [12][13][14][15][16][17][18] Moreover, a comparison of the data from the literature regarding frequency and severity of dental erosion is hindered by the use of various scoring systems (e.g., the Eccles index, Tooth Wear index by Smith and Knight, Simplified-Tooth Wear Index, Evaluating Index of Dental Erosion, index by O'Brien, index by Lussi, index by O'Sullivan and BEWE scoring system). 19,20 In Polish youth, erosive lesions occurred at close to the same rate as those reported in the literature, aged 15 years 24.7% and aged 18 years 42.3% (evaluation according to the BEWE index).…”
Section: Discussionmentioning
confidence: 99%
“…The observed increase of dental erosion frequency along with the age of the subjects was noticed in previously published papers. 13,18 It probably resulted from longer time of the teeth's presence in the oral environment and longer exposure onto erosive factors. An earlier study performed in 12-year-olds from Wrocław with use of the index by Lussi showed lower than the current erosion frequency (8.3% vs 12.7%), which could suggest a progressive increase of this pathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation